The Influence Of The @Ikom_Telu Instagram Account Strategy In Fulfilling The Information Needs Of Telkom University Communications Science Students - Pratama, Okta Andika; Putri, Idola Perdini (eProceedings of Management, 2025)
Indonesia, a global population leader, experiences a surge in digital technology use. Datareportal.com's